The Initial Mass Function of Young Open Clusters in the Galaxy: A Preliminary Result. Issue Volume 12:Issue S316(2015) (31st March 2017) - Lim, Beomdu; Sung, Hwankyung; Hur, Hyeonoh; Park, Byeong-Gon
Abstract: The initial mass function (IMF) is an essential tool with which to study star formation processes. We have initiated the photometric survey of young open clusters in the Galaxy, from which the stellar IMFs are obtained in a homogeneous way. A total of 16 famous young open clusters have preferentially been studied up to now. These clusters have a wide range of surface densities (log σ = −1 to 3 [stars pc −2 ] for stars with mass larger than 5 M ⊙ ) and cluster masses ( M cl = 165 to 50, 000 M ⊙ ), and also are distributed in five different spiral arms in the Galaxy. It is possible to test the dependence of star formation processes on the global properties of individual clusters or environmental conditions. We present a preliminary result on the variation of the IMF in this paper.